Nasionalisme dalam QS. At-Taubah 122 (Analisis Nilai-Nilai Kebangsaan dalam Anime Naruto) - Ahmad Zaini; Anas Muchtar (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
Nationalism, as an expression of love for one’s homeland, is a natural human disposition and an integral part of Islamic teachings that aligns with one’s devotion to religion. This value has inspired scholars, clerics, and religious figures to resist colonialism through a spirit of struggle intertwined with Islamic principles. This study aims to explore the values of nationalism contained in QS. At-Taubah verse 122 and analyze the harmony of these values with the representation of patriotic spirit in several scenes of the anime Naruto. Another objective is to emphasize that a sense of nationalism can grow through understanding both religious teachings and popular culture that share similar moral values. The research employs a library research approach with a content analysis method. Data were collected through documentary techniques using written sources such as Qur’anic exegesis, Islamic literature, and popular media relevant to the theme of nationalism. The results indicate that QS. At-Taubah verse 122 embodies the value of nationalism, manifested through the call to deepen knowledge as a form of responsibility toward the community and the nation. This value parallels the spirit of Naruto characters who strive for peace and the progress of their village. The study identifies a research gap in previous works that seldom connect Islamic values with Japanese popular culture. This research contributes new insights by bridging religious values and popular media as tools for fostering nationalism in the era of globalization.